Photography, Modernity and the Governed in Late-colonial Indonesia - Protschky, Susie (Amsterdam University Press, 2015)
The essays in this volume examine, from a historical perspective, how contested notions of modernity, civilization, and being governed were envisioned through photography in early twentieth-century Indonesia, a period when the Dutch colonial regime was implementing a liberal reform program known as the Ethical Policy. The contributors reveal how the camera evoked diverse, often contradictory modes of envisioning an ethically governed colony, one in which the very concepts of modernity and civilization were subject to dispute.